A model for quantitative security measurement and prioritisation of vulnerability mitigation. (20th November 2013) - Tripathi, Anshu; Singh, Umesh Kumar
Quantitative security measurement is an essential step in managing security proactively. This measurement can help system administrator in making optimal decisions about mitigation of security risks posed by presence of vulnerabilities. Quantifying security risks using security metrics is an important and yet challenging task, as metrics exists for individual vulnerabilities but how to aggregate these metrics is still an unresolved issue. In this paper, we propose a quantitative security measurement model that measures security level of hosts in the network by aggregating risk levels of vulnerabilities in a meaningful manner. Further, proposed model guides system administrator in prioritising vulnerability mitigation by evaluating relative risk level of vulnerabilities in the network. Proposed model produces quantitative security metrics that provide rapid and consistent security measurement, hence aid in automated and reasonable security management. A case study is presented to demonstrate the efficacy of proposed model.